Implementation of Principal Managerial Supervision in Improving School Performance at The State Vocational School of Aceh Besar Regency - Sufrida Sufrida; Yusrizal Yusrizal; Nasir Usman (AL-ISHLAH: Jurnal Pendidikan, 2022)
Principals as supervisors are required to have knowledge, attitudes, and skills in management and leadership so that they can carry out their duties, in this case carrying out managerial supervision. This study aims to explain the principal's managerial supervision program in improving school performance, implementation of managerial supervision, evaluation of the implementation of managerial supervision, and factors that influence the success and obstacles in implementing managerial supervision in schools. This study uses a descriptive qualitative approach, with data collection techniques through observation, interviews and documentation studies. The research subjects were the principal, vice principal, teachers and school supervisors. The research results show that: (1) The school program is prepared or planned at the time of the new school year work meeting, which contains the principal's supervision program. The supervision program includes a schedule for the implementation of supervision; (2) managerial supervision by the principal in its implementation has not been so maximal; (3) Evaluation of managerial supervision is carried out by looking at the performance of teachers and staff. Meanwhile, the follow-up actions taken are verbal warnings, other than personal reprimands will also be delivered at a general meeting; (4) Supporting factors include support from the local government, the education office and school supervisors as well as the willingness of school residents to learn and improve their quality. Inhibiting factors include the limited time of the principal and also the lack of community support for the school.